Review Of The Level Of Physical Fitness Of 34 Padang Junior School Students - Mardiansyah, Mardiansyah; Jonni, Jonni; M, Madri (Jurnal Guru Peneliti Professional, 2018)
This research has a starting point from the lack of Physical Fitness level of students at SMP Negeri 34 Padang. Possible causes include a lack of movement activity among these school students. This study aims to: determine the level of physical fitness of SMP Negeri 34 Padang. This research was conducted at the SMP. This type of research is a descriptive analysis that aims to reveal the level of physical fitness of the students of SMP Negeri 34 Padang. When the study began in August 2017. The population of the study was 110 people. Sampling was done by using the Random Sample Technique, namely: class VII and VIII female students, so the sample consisted of 28 students of SMPN 34 Padang. From the data analysis, the results obtained were as follows: Physical fitness level of 34 Padang State Junior High School Students who were in the moderate classification (64.3%) of students, and poor classification (35.7%). From these findings it can be concluded that: the level of physical fitness of students at SMP Negeri 34 Padang is classified as moderate.Abstract english version, written using Time New Roman-11, italic. Abstract containsresearch aim/purpose, method, and reseach results; written in 1 paragraph, single space among rows, using past tense sentences.